Mobile-Based Learning to Increase The Motivation of Learning Students of State Vocational School 2 Gorontalo - Syaifuddin Lily; Hamka Witri Kamase (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2021)
Learning System in Indonesia is carried out with a face-to-face system, teaching and learning activities are carried out in schools in one room. The widespread pandemic of the covid 19 virus made the Ministry of Education and Culture take a policy to conduct online school activities to prevent the transmission of the disease virus. Online learning does not all have to be done using Zoom or similar applications. It is also necessary that applications that schools can manage and uniformize their use so that teachers can quickly fill out materials and tasks. The learning system carried out in SMK Negeri 2 Gorontalo is considered less effective, affecting learning outcomes. The application created is an application that can help the learning and teaching process in SMK Negeri 2 Gorontalo. Learning media is expected to help facilitate the absorption of the material and the delivery of lesson content to increase students' motivation to learn and understand it anywhere and anytime. The method used is the Research and Development method. As a research method used to produce a particular product and test the effectiveness of the product where the object of research in the study is a Student at SmK Negeri 2 Gorontalo. The purpose of the study is to help increase students' learning motivation in times of pandemics.